THEORETICAL ASPECTS OF THE METHODOLOGICAL SYSTEM OF TRAINING MATHEMATICS TEACHERS (Scientific journal of the Fergana State University, 2023)
This article is devoted to the issues of training modern teachers of mathematics, the development of the ability to apply the knowledge received by a mathematics teacher in the process of professional activity and their role in the process of professional activity is sufficiently disclosed.